Solving for Project Risk Management - Smart, Christian (McGraw Hill-Ascent Audio, 2021)
All projects, large and small, are subject to various risks. But the failure to manage inherent risk with diligence and know-how can lead to devastating consequences for an organization. In this comprehensive hands-on guide, a renowned expert in the field provides everything organizations need to conduct project risk management the right way. Why do so many projects come in over schedule and over budget? How do projected expenditures and schedules line up with reality? How can you accurately assess risk to mitigate financial disaster? Through a methodical, statistics-based approach, Christian B. Smart reveals: the enduring problem of cost and schedule growth; how rigorous project risk management can reduce the impact of uncertainty; the systematic tendency to underestimate risk-and how to avoid it; ways to accurately assess confidence levels in project risk management; and the need for proper risk management at the portfolio level. The author lays out common problems and explains how to effectively solve them. Ideal for project managers, business analysts, and senior decision makers in both the public and private sectors, Solving for Project Risk Management offers everything you need to ensure your projects run smoothly, on budget, and deliver the expected outcomes.
Online resource; Title from title page (viewed September 14, 2021)
Keywords: Audiobooks; Livres audio